PERBANDINGAN PREVALENSI CACING GASTROINTESTINAL PADA SAPI BALI DAN LOKAL DI KABUPATEN BANGGAI - WAHYUDIN ABDUL KARIM; ABDUL MUIN KENTA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2018)
The studies of gastrointestinal worm in cow have not been widely explored in Distric Luwuk Banggai. This study was aimed to Comparison of Prevalence of Gastrointestinal Worms in Bali and Local Cows in Banggai District. The fresh faecal samples were collected from 70 cows and observed by a modified McMaster technique. The faecal of cows were collected in south Luwuk, east Luwuk, North Luwuk, Manucipility Masama, Lamala, and Bualemo. The result of identification on gastrointestinal worm show that there were six genera of helminth i.e Moniezia, Haemonchus, Bunostomum, Oesophagostomum, Trichostrongylus, dan Capillaria. The prevalence in female was higher than male. The prevalence in kinds of cow was higher ongole cow than cow Bali.